2016
DOI: 10.1371/journal.pone.0150580
|View full text |Cite
|
Sign up to set email alerts
|

Health Related Behaviours in Normal Weight and Overweight Preschoolers of a Large Pan-European Sample: The ToyBox-Study

Abstract: The aim of this study was to investigate the associations of health related behaviours (HRB) with Body Mass Index (BMI) in preschoolers, and to study the likelihood of being overweight/obese in relation to compliance with recommended HRB. The sample consisted of 3301 normal weight and overweight/obese preschoolers (mean age: 4.7 years; 52% boys, 85% normal weight) from six European countries (Belgium, Bulgaria, Germany, Greece, Poland, Spain). Height and weight were measured, total daily step counts were regis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
37
4
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 28 publications
(46 citation statements)
references
References 39 publications
4
37
4
1
Order By: Relevance
“…The pedometer-determined PA in Czech pre-schoolers did not reveal weekdayweekend-related differences in daily step counts. This finding is in contrast to other current European (Cardon et al, 2016;De Craemer, Lateva, et al, 2015) and American studies (Craig et al, 2013). Other studies of weekly PA in pre-schoolers repeatedly observed higher step counts on weekdays than at weekends (Cardon et al, 2016;De Craemer, Lateva, et al, 2015).…”
Section: Discussioncontrasting
confidence: 86%
See 1 more Smart Citation
“…The pedometer-determined PA in Czech pre-schoolers did not reveal weekdayweekend-related differences in daily step counts. This finding is in contrast to other current European (Cardon et al, 2016;De Craemer, Lateva, et al, 2015) and American studies (Craig et al, 2013). Other studies of weekly PA in pre-schoolers repeatedly observed higher step counts on weekdays than at weekends (Cardon et al, 2016;De Craemer, Lateva, et al, 2015).…”
Section: Discussioncontrasting
confidence: 86%
“…Previous comprehensive studies of energy balance-related behaviours in preschool children from six European countries (Belgium, Bulgaria, Germany, Greece, Poland, and Spain) (Cardon et al, 2016;De Craemer, Lateva, et al, 2015; used objectively measured overweight status, PA measured by pedometers, and parents' proxy-reported questionnaires for assessing the sedentary behaviour and dietary habits of pre-schoolers (Cardon et al, 2016). However, the aforementioned studies (Cardon et al, 2016;De Craemer, Lateva, et al, 2015) did not use a strict inclusion criterion for PA regarding the number of days of pedometer-monitored PA of pre-schoolers (e.g. a minimum of two weekdays and one weekend day).…”
Section: Introductionmentioning
confidence: 99%
“…We also did not find any significant association between exclusive breastfeeding and overweight/obesity, which is in line with the systematic review of systematic reviews by Patro-Gołąb et al [26] and indicates that in addition to feeding practices during infancy (i.e., breastfeeding or formula feeding) there are also other EBRBs occurring after the initiation of complementary feeding that may exert an equally significant effect on children's weight status. Regarding the EBRBs assessed in our study, the time preschoolers spend engaged in active play and screen-related activities were found to be associated with preschoolers' overweight/obesity, a finding that has also been confirmed by other previous studies conducted with preschool children [6,27]. The associations of preschoolers' overweight and obesity with region and parental weight status retained their statistical significance after controlling for perinatal factors and children's EBRBs.…”
Section: Tablesupporting
confidence: 89%
“…Similar to perinatal risk factors, EBRBs seem to be influenced also by regional and sociodemographic variations [7,14]. This observation could be further supported by recent findings from the ToyBox study, indicating unhealthier EBRBs in southern European countries, with Greek preschool children having significantly lower physical activity levels and, at the same time, significantly more time spent on sedentary activities compared with their peers in central/northern European countries [6]. Furthermore, the ToyBox study has also found that maternal education is positively associated with children's diet quality, with children of lower-educated mothers having lower diet quality compared with children whose mother had higher education [15].…”
Section: Introductionmentioning
confidence: 61%
See 1 more Smart Citation